Hubungan Profil Pelajar Pancasila dalam Kerangka Merdeka Belajar terhadap Kemampuan Literasi Matematis Peserta Didik - Hardianti, Desrina; Asnawati, Rini; Utami, Lintang Fitra; Asyhara, Suryatul Aini; Lestari, Fitria (Jurnal Pendidikan Matematika Universitas Lampung, 2025)
This study was conducted to determine the relationship between the Pancasila student profile and students' mathematical literacy skills and to determine the Pancasila student profile affects mathematical literacy skills. Therefore, the data were analyzed using a simple linear regression test because it only involved 1 sample group. The sample in this study was 31 students of class X of the 2024/2025 academic year at a high school or equivalent in Pesawaran, Lampung. The sample determination was carried out using a purposive sampling technique because the researcher could not change the class that had been determined by the school. We chose the school as our research object because it had implemented the independent learning curriculum. Data collection was carried out using test techniques and the Pancasila student profile scale. The findings of the study indicated that no relationship between the Pancasila student profile and students' mathematical literacy. Based on the R Square value, which is 0.001, it shows that the influence of the Pancasila student profile on students' mathematical literacy is 0.1% and 99.9% is influenced by other variables that are not studied. The study was limited to finding out whether there is a relationship between the Pancasila student profile and students' mathematical literacy skills, and knowing to what extent the two variables influence.